Tinjauan Yuridis Perlindungan Pemberi Waralaba Atas Wanprestasi Penerima Waralaba Dalam Perjanjian Waralaba - Putri, Tiara Shafa; i, Urbanisasi (Peneliti.net, 2023)
The franchise agreement which forms the basis for the implementation of the franchise made by the franchisor and the franchisee clearly states the rights and obligations of each party. It is possible that the agreement entered into by the franchisor and the franchisee may face cases of default by one of the parties. An example of default that can occur is when the franchisee does not pay the required royalty fees. The method used in this paper is normative law. Based on the results of the writing, the franchisor gets protection for his interests, namely the right to receive royalty fees from the franchisee. The purpose of this writing is to understand what kind of legal protection the franchisor has as a victim of default by the franchisor for not paying royalty fees.